Discovering the basic social process of empowerment in health among families in relocation communities - Sumile, Earl Francis R. (Manila College of Nursing, University of the Philippines Manila, 2018)
Health is a multidimensional phenomenon influenced by factors in and out of the human body. The science of nursing, following the works of Florence Nightingale advocates for a milieu conducive to health. Working with communities and population groups, nurses strive to contribute to the goals of health promotion and disease prevention. The Alma Ata declaration of Primary Health Care (1978) speaks of an approach to peoples’ health by helping communities take responsibility for their health through their full participation and in the spirit of self-reliance and self-determination. The province of Bulacan, due to its proximity to Metro Manila has been the cradle of relocation sites for poor families affected by either calamities or urban development in cities. These relocation communities offer a unique scenario of poor access to healthcare that contributes to powerlessness . Thus, the need to understand how families in relocation communities take control of their healthcare needs remain a paramount concern. Their journey of empowerment on health is fittingly shared through their own words and explicated as a social process, and such in the objective of this qualitative research.

The study was conducted among theoretically-selected lay adult lay adult members of selected relocation communities in the province of Bulacan, who have been in direct involvement with their organization or committee. Data collection, primarily through focus groups discussions, was conducted iteratively until data saturation has been achieved. Subsequently, key informant interviews were also employed to achieve congruence and verification with previously collected data. Employing the Classic Grounded Theory (CGT) approach, transcribed narratives were analyzed through constant comparison technique and open, selective, and theoretical coding.

Results of data analysis revealed that families in relocation communities suffer from the basic social problem of marginalization due to poor access to healthcare, neglect from authorities, and burden of disease. A total of 1,086 in vivo codes were generated that were reduced to 24 categories, and then collapsed further according to fit to yield 7 key concepts that led to the emergence of the core category of self-reliance. The result of this study is the discovery of the substantive theory of Gaining Control over Marginalization which illustrates empowerment in health among relocation communities. There are Five (5) C’s in the basic social process of self-reliance namely: Consciousness rising, Capacity building, Committing to serve, Carrying out responsibilities, and Collaborating. This substantive theory has implications to nursing practice, education and research. Primarily, this theory encourages nurses to give premium on engaging communities to actively participate in activities that will promote their own health. This can be achieved through small scale organizing initiatives among population groups like women and elderly. Moreover, the experience of families in relocation communities showed how they were strongly influenced by attending seminars and trainings on health. Hence, nurses should capitalize on health education activities to influence people in communities to value health and assume responsibility for it. Member checking, critical friend technique, audit trail, and data triangulation were employed to ensure rigor and trustworthiness.
Dissertation (Doctor of Philosophy in Nursing) -- University of the Philippines Manila, June 2018.
Bibliography: leaves 107-114.
Keywords: Relocation (Housing) -- Health aspects